Enhanced multi-antenna capabilities through small cell collaboration - Finn, Danny (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2015)
This thesis shows that collaboration between base stations in small cell scenarios can lead to enhanced multiple-antenna gains. We demonstrate this for the case of multi-user MIMO-based reassignments between adjacent small cells, from the perspectives of spectral efficiency, energy efficiency and number of spatial layers effectively utilised.
Keywords: Electronic & Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin